First report of feeding traces in Permian Botrychiopsis leaves from western Gondwana - Pinheiro, Esther R. S. (2015)
The genus Botrychiopsis consists of leaves with substantial heteromorphism, present in late Paleozoic Gondwanan floras. The genus is recorded in paleofloras from Australia, India, South Africa, Brazil, and Argentina, and occurs from the latest Mississippian to the early Permian. Here, we report and analyze the first record of plant-insect interactions found in the Botrychiopsis-type leaves from the basinal deposits of Permian Argentina and Brazil. The samples are from three different Permian deposits: Arroyo Totoral, Bajo de Véliz (Argentina), and Morro do Papaléo (Brazil). Evidence of insect-plant interactions was present in only eight of 154 specimens analyzed. We found evidence of margin and hole feeding damage made by insects. This represents the first evidence of plant-insect interactions in Botrychiopsis leaves from Permian Gondwanan deposits. The occurrence of herbivory only on the Permian species B. plantiana may indicate that consumption of these leaves began during this interval, not in the Carboniferous, as occurred with Cordaites leaves.